Transformative Intelligence : The Evolving Role of AI in Modern Financial Services - Deepu Komati, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the multifaceted impact of artificial intelligence on the financial services industry, analyzing its applications across credit risk assessment, collections management, fraud detection, and personalized banking. Through a comprehensive review of current implementations, The article demonstrates how machine learning models enable financial institutions to process and analyze unprecedented volumes of data, resulting in more accurate risk assessments and fraud prevention capabilities. The article explores how AI-driven customer segmentation and behavioral analysis transform collection strategies while maintaining positive customer relationships. Furthermore, the article investigates how these technologies enhance operational efficiency and regulatory compliance while delivering more personalized financial experiences. The article suggests that financial institutions implementing AI solutions are experiencing significant competitive advantages through improved decision-making processes, enhanced security frameworks, and more customer-centric service models. This transformation represents a fundamental shift in how financial services are developed, delivered, and experienced in the modern marketplace.
Keywords: Financial Technology; Machine Learning; Credit Risk Assessment; Personalized Banking; Fraud Detection